A commentary of "The brain evolutionary mechanism of feeding preference": 10 remarkable discoveries from 2020 in Nature. - Pan, Y. (Fundamental research, 2022)
The fly Drosophila sechellia feeds exclusively on the toxic noni fruit (Morinda citrifolia). What makes this species such a picky eater compared with its generalist relatives? Auer et al. cracked the case using the genome-editing tool CRISPR/Cas9 [1]. One sensory neuron class expressing the odorant receptor 22a (Or22a) protein is more abundant in D. sechellia than in other fly species. The group established that small changes in Or22a's amino-acid sequence have contributed to D. sechellia's preference for noni. They also identified several other evolutionary changes that might contribute to this apparently simple behavioral shift. Even tiny flies that love stinky fruit can provide powerful insight into how brains evolve to shape complex behaviors.